Gender differences in vision health-seeking behavior and vision health outcomes among rural Chinese schoolchildren by birth order and family size - Yunyun Zhang; Hongyu Guan; Yuxiu Ding; Jing Xue (BMC, 2023)
Abstract Background The gender gap remains a major impediment in the path toward equality, and it is especially wide in low-income countries. Gender differences in health-seeking behaviors may be a factor. Family size and childbirth order are two critical factors affecting family resource allocation. This study examines gender differences in healthcare-seeking behaviors among children with visual impairment in rural China across different family structures (birth order and family size). Methods We draw on a dataset containing 19,934 observations constructed by combining data from 252 different school-level surveys spanning two provinces. The surveys were all conducted in 2012 using uniform survey instruments and data collection protocols in randomly selected schools across western provinces in rural China. The sample children range in grades from 4 to 5. Our analysis compares rural girls with rural boys regarding vision health outcome and behavior (vision examination and correction). Results The findings revealed that girls have worse vision than boys. Regarding vision health behaviors, girls have a lower overall vision examination rate than boys. There is no gender difference when the sample student is the only child or the youngest child in the family, but there is still a gender difference when the sample student is the oldest child in the family or the middle child in the birth order. When it comes to vision correction behavior, boys are more likely to own eyeglasses than girls are for groups of students with mild visual impairment, even when the sample student is the only child in the family. However, when the sample student has another brother or sister (the sample student is the youngest, the oldest child in the family, or the middle child in the birth order), the gender difference disappears. Conclusions Gender differences in vision health outcomes are correlated with gender differences in vision health-seeking behaviors among rural children. Depending on the birth order and family size, gender disparities in visual health practices vary. In the future, consideration should be given to providing medical subsidies to reduce the cost of vision health behaviors and to provide information interventions to change gender inequality in households and promote equality in children's vision health behaviors. Trial registration The trial was approved by the Stanford University Institutional Review Board (Protocol No. ISRCTN03252665). Permission was received from local Boards of Education in each region and the principals of all schools. The principles of the Declaration of Helsinki were followed throughout. Written informed consent was obtained from at least one parent for all child participants.